Perioperative Respiratory Outcome of Patients with Eosinophilia: A Cohort Study in a Tertiary Care Hospital. (10th January 2023) - Lyngdoh, Nari M.; Thabah, Rajani; Aggarwal, Sunny; Sailo, Laltanpuii; Shakya, Raju; Wahlang, Julie; Shylla, Badondor; Naskar, Chhandasi
Abstract : Background . A respiratory adverse event is one of the main causes of critical events in the perioperative period. Perioperative distress symptoms like cough and stridor have been reported to occur in patients with hyperreactive airways. Objective . This study was conducted to determine the relationship between blood eosinophil count and perioperative adverse respiratory events among different age groups of patients who require general anesthesia for different types of surgeries. Methods . A cohort study was conducted on 197 patients of either gender, aged 3 years and above, belonging to ASA classes I–II, who were scheduled to undergo surgery requiring general anesthesia and intubation. Patients were stratified according to absolute eosinophil count into two groups: Group A (AEC 0 to 499/mm 3 ) and Group B (AEC 500 to 1000/mm 3 ). Patients were monitored for 24 hours in the perioperative period for adverse respiratory events such as bronchospasm, laryngospasm, a fall in SPO2 < 95%, and cough and stridor. Results . A total of 197 patients were evaluated, with a median age of 37 ± 14.4 years. The percentage range of adverse respiratory events across different age groups was 35% in adults to 60% in children. Major complications noted were a fall in SPO2 < 95% (62.5%) and cough (27.7%) as per CTCAE v5.0 (November 27, 2017). The Naranjo score of adverse respiratory events was categorized as possible with mild level 1 severity. Adverse respiratory events were managed with humidified oxygen, antitussives, and bronchodilators. Conclusions . Eosinophilia is seen in one-third of the patients undergoing surgical interventions. Patients with a blood eosinophil count of ≥400/mm 3 had an increased risk of exacerbations of respiratory adverse events in the perioperative period.